Greenhouse gas emissions from Uganda's cattle corridor farming systems - Kiggundu, Nicholas; Ddungu, Stanley Peter; Wanyama, Joshua; Cherotich, Sam; Mpairwe, Denis; Zziwa, Emmanuel; Mutebi, Faizal; Falcucci, Alessandra (Agricultural systems, 2019)
The objective of this study was to estimate the greenhouse gas (GHG) emissions from practised cattle farming systems (Stall, Semi-Intensive, Grazing, Tethering and Scavenging) and identify potential areas for GHG mitigation. Using the Global Livestock Environmental Assessment Model (GLEAM-i), GHG emissions in 2016 were 2009 Gg CO2-eq/yr of which the Grazing system contributed 88.5%. Enteric fermentation produced about 75.8% of the total GHG emissions. At an annual growth rate of 3%, the projected GHG for 2020 and 2025 would increase by 12.6% and 30.7% respectively. The milk and meat emission intensities were far higher than the global averages. A reduction in grazing by 10% and a 10% increase in use of anaerobic digesters to handle manure resulted in a 4.4% reduction in annual GHG emission.
Keywords: Greenhouse gases; Emission; GLEAM-i; Cattle farming systems; Manure management